(untitled) (ASEAN Engineering Journal, 2018)
Manganese (Mn) is an important metal in producing a good quality steel, that the total Mn consumption in this industry reaches 85 to 90%. Despite of this huge demand, Mn faces a shortage supply due to depletion of high grade Mn ore. As an alternative, low grade manganese ore (LGMO) can be utilized to fulfill the industry demand. The aim of this work is to determine the optimum condition of the reductive leaching process of LGMO using Response Surface Methodology (RSM). The design of experiment (DOE) was made using RSM by Central Composite Design (CCD) with 22 and 3 central points. In this work, the effect of variables such as sulphuric acid concentration (X1) and weight of glucose (X2) were examined. The experimental data obtained from Analysis of Variance (ANOVA) were analyzed. Subsequently, the most significant variable was identified and fitted into a quadratic model. It is found that the interaction between sulphuric acid concentration and amount of glucose (X1X2) is the most important factor in manganese (Mn) extraction. The optimum leaching condition is obtained at 2.5 M sulphuric acid concentration and 2 g weight of glucose at 60 minutes leaching time. Within this experimental condition, a high level of Mn extraction ratio at 88.97% is achieved.